2015
DOI: 10.1016/j.aat.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia, surgical stress, and “long-term” outcomes

Abstract: An increasing body of evidence shows that the choice of anesthetic can strongly influence more than simply the quality of anesthesia. Regional and general anesthesia have often been compared to ascertain whether one provides benefits through dampening the stress response or harms by accelerating cancer progression. Regional anesthesia offers considerable advantages, by suppressing cortisol and catecholamine levels and reducing muscle breakdown postoperatively. It also has less immunosuppressive effect and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
59
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 67 publications
(62 reference statements)
1
59
1
7
Order By: Relevance
“…Está ampliamente demostrado que el dolor y ansiedad perioperatorios se asocian a una exacerbación de la respuesta al estrés, con las subsecuentes elevaciones en glicemia, activación del sistema simpático y complicaciones tromboembólicas, isquémicas e inmunológicas (20,21). Por otro lado, una sedación excesiva también puede repercutir negativamente, dada la probabilidad de depresion respiratoria y requerimiento de ventilación mecánica, con la posible necesidad de hospitalización en unidad de cuidado intensivo (16,20,22).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Está ampliamente demostrado que el dolor y ansiedad perioperatorios se asocian a una exacerbación de la respuesta al estrés, con las subsecuentes elevaciones en glicemia, activación del sistema simpático y complicaciones tromboembólicas, isquémicas e inmunológicas (20,21). Por otro lado, una sedación excesiva también puede repercutir negativamente, dada la probabilidad de depresion respiratoria y requerimiento de ventilación mecánica, con la posible necesidad de hospitalización en unidad de cuidado intensivo (16,20,22).…”
Section: Discussionunclassified
“…Por otro lado, una sedación excesiva también puede repercutir negativamente, dada la probabilidad de depresion respiratoria y requerimiento de ventilación mecánica, con la posible necesidad de hospitalización en unidad de cuidado intensivo (16,20,22).…”
Section: Discussionunclassified
“…We can conclude that epidural analgesia positively affects the immune system, preventing severe postoperative immuno suppression, which is particularly due to the increase in the number of CD-3-cells, B-cells, CD4/ CD8 ratio, and partially of NK-cells. In a previous study, higher cortisol levels postoperatively were shown to be associated with a higher chance of developing POCD [4,5,7,8] . Epidural anesthesia has an important influence on the modulation of the immune response in patients who underwent major orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative cognitive dysfunction (POCD) is a major consequence of this. It is essentially "deterioration in cognition temporally associated with surgery" [4,5] , and might lead to a higher mortality rate within three post-operative months [6] . A number of studies have revealed that the inflammatory response is a key factor in the development of postoperative cognitive dysfunction (POCD) [7][8][9][10] .…”
mentioning
confidence: 99%
See 1 more Smart Citation